2013
DOI: 10.1002/cplu.201300104
|View full text |Cite
|
Sign up to set email alerts
|

The Reaction and Materials Chemistry of [Sn6(O)4(OSiMe3)4]: Chemical Vapour Deposition of Tin Oxide

Abstract: [Sn6(O)4(OSiMe3)4] and [{Sn(OSiMe3)2}2] have been used to deposit SnO thin films by chemical vapour deposition. Films derived from [Sn6(O)4(OSiMe3)4] comprise uniform cubes and are highly oriented, whereas those deposited from [{Sn(OSiMe3)2}2] are made up of a continuous non‐oriented layer with oriented cubes on the surface. The structure of a co‐crystal, 2 Sn6(O)4(OSiMe3)4⋅[Sn(OSiMe3)2]2⋅4 THF, shows that [{Sn(OSiMe3)2}2], a liquid at room temperature, adopts a μ‐OSiMe3‐bridged dimeric structure. [Sn6(O)4(OSi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 33 publications
(51 reference statements)
1
23
0
Order By: Relevance
“…Other dopants for SnO 2 have also been investigated, including Mg in an attempt to achieve high conductivity and transparency. 220 Powder XRD confirmed the formation of SnO (and no Sn metal), which was surprising given the higher temperatures used in these depositions. A stannous ureid compound (Fig.…”
Section: Ternary Main Group Tcosmentioning
confidence: 94%
“…Other dopants for SnO 2 have also been investigated, including Mg in an attempt to achieve high conductivity and transparency. 220 Powder XRD confirmed the formation of SnO (and no Sn metal), which was surprising given the higher temperatures used in these depositions. A stannous ureid compound (Fig.…”
Section: Ternary Main Group Tcosmentioning
confidence: 94%
“…Meanwhile, among the contents of Table , the atomic‐layer deposition (ALD) method has been demonstrated by Han et al for growing p‐type SnO thin films, showing a polycrystalline structure and Hall mobility of 2.9 cm 2 V −1 s −1 . Besides ALD, chemical routes like chemical vapor deposition (CVD) and aerosol‐assisted CVD have also been successfully employed in the fabrication of the SnO thin films; however, no Hall measurement results were shown …”
Section: Discovery and Synthesis Of Hole‐transporting (P‐type) Oxidesmentioning
confidence: 99%
“…SnO thin films have also been deposited using [Sn 6 (O) 4 (OSiMe 3 ) 4 ]a nd [{Sn(OSiMe 3 ) 2 } 2 ]a st he Sn ligands. [37] In these reactions, it was found that the temperature of deposition was key to achieving SnO thin films. At ad eposition temperatureo f450 8C, SnO thin films were achieved from both of the precursors.…”
Section: Deposition Of Binary Metal Oxide and Dopedmetal Oxide Materialsmentioning
confidence: 99%